Coarse‐grained methods for polymeric materials: enthalpy‐ and entropy‐driven models. (10th May 2013) - Carbone, Paola; Avendaño, Carlos
Abstract : Abstract : Polymers are multiscale systems by construction. They are formed by several monomeric units connected by covalent bonds whose chemical nature defines the rigidity of the chain. The interconnection between the monomeric units determines the interdependence of the motion of the different chain segments and the intrinsic multiscale nature of polymeric materials. This characteristic is reflected on the different modeling techniques that can be used to simulate polymeric materials. Because of the large conformational space that needs to be sampled when simulating polymers, coarse‐grained (CG) models are commonly used and depending on which part of the system free energy (enthalpy, entropy, or both) is relevant for the properties of interest, the appropriate modeling techniques should be used. Each model is characterized by advantages and limitations that can have a great impact on the quality of the results obtained. In this overview, we address some of the more common CG techniques presented in the literature for the modeling of polymeric materials at different length scales. WIREs Comput Mol Sci 2014, 4:62–70. doi: 10.1002/wcms.1149 This article is categorized under: Molecular and Statistical Mechanics > Molecular Dynamics and Monte-Carlo Methods